Blog educacional para o ensino das danças folclóricas a partir do currículo de educação física do estado de São Paulo - Diniz, Irlla Karla dos Santos [UNESP] (2014)
Dance as one of the contents of body culture still struggles to penetrate the walls of the school. The Physical Education teachers for not having experience with this issue, both before and after graduation, still face limitations to treat it in a contextualized way. The curriculum, resulting in a selection within the culture, makes a cut of knowledge that must be thematized in school, giving teachers an overview of the contents, and acting as guiding the curriculum components. The Physical Education Curriculum of the State of São Paulo, newly established presents dance as any of its contents, however, the didactic -pedagogical treatment offered seems synthesized in a few moments. Thus, some pedagogic possibilities to contribute to the work of the teacher already facing so many difficulties in the school environment were investigated. Given the new context that is established, we sought to invest in the use of Information Technology and Communication (ICT) to provide teachers knowledge and complementary possibilities for treating dance in their classes. ICT in the educational context can provide a more comprehensive elaboration of knowledge, expanding the sources of information, and providing the teacher treat content that often is not present within the Physical Education classes. Therefore, the aim of this study was to develop and evaluate a complementary teaching material to the Physical Education Curriculum of the State of São Paulo, in the form of an educational blog which subsidize the work of teachers in the content of folk dances proposed for the seventh year of elementary school. This material was published and disseminated in the form of an educational blog, which subsequently was evaluated by six teachers of Physical Education of the State of São Paulo. In addition, two participants in this group taught classes of folk dances from the proposed blog content, experimenting in real teaching situations the possibilities of the...